THE EFFECT OF SWIRL NUMBER ON DISCHARGE COEFFICIENT FOR VARIOUS ORIFICE SIZES IN A BURNER SYSTEM (Jurnal Mekanikal, 2018)
A liquid fuel burner system with different orifice plate sizes mounted at the exit plane of the airswirler outlet has been investigated using a 140 mm inside diameter combustor of 400 mm length. Three different orifice plate diameters of 45 mm, 40 mm and 35 mm were used with a 10Ëš to 70Ëš radial air swirler vane angles. The purpose of orifice plate insertion is to create the swirler pressure loss at the swirler outlet so that the swirler outlet shear layer turbulence could be maximized to assist in the mixing of fuel and air. Measurements of air flow rates, air inlet temperature, air inlet pressure and pressure drop across the combustor have been carried out to predict the isothermal characteristics inside the combustor, ie. discharge coefficient. The result shows that the discharge coefficient decreases as the swirl number increases for all three different orifice plate sizes.
Keywords: Swirler; orifice plate; pressure drop; swirl number; discharge coefficient